2008
DOI: 10.1364/oe.16.020891
|View full text |Cite
|
Sign up to set email alerts
|

Polarization distortion effects in polarimetric two-photon microscopy

Abstract: We present a global analysis of experimental factors affecting polarization responses in two-photon inverted microscopy. The role of reflection optics and high numerical aperture focusing is investigated in two-photon fluorescence, which can be extended to other nonlinear processes. We show that both effects strongly distort polarization responses and can lead to misleading extraction of molecular order information from polarimetric measurements. We describe a model accounting for these effects and develop a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The approach of having the LCM in the infinity space is more accurate and convenient than rotating the polarization outside the microscope, as birefringence in the system will result in erroneous states at the focus. This is also simpler than finding a solution for every desired polarization state [27,28]. We note that Oldenbourg first used liquid crystals to achieve universal compensation in the PolScope in 1995 [37].…”
Section: Advantages Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach of having the LCM in the infinity space is more accurate and convenient than rotating the polarization outside the microscope, as birefringence in the system will result in erroneous states at the focus. This is also simpler than finding a solution for every desired polarization state [27,28]. We note that Oldenbourg first used liquid crystals to achieve universal compensation in the PolScope in 1995 [37].…”
Section: Advantages Of the Methodsmentioning
confidence: 99%
“…As a solution, Chen and associates [27] used the combination of a half and a quarter waveplate to pre-compensate for the elliptical distortion at each linear polarization rotation angle, but the compensation requires a nonlinear solution and this approach is not practical. Similarly Brasselet investigated the polarization distortion effect on SHG polarization resolved microscopy and used a distortion response model to calibrate the system [28]. As a simpler alternative, we have previously placed a polarizing beamsplitting (PBS) cube in the infinity space and rotated the sample mounted on a circular-centered stage [29].…”
Section: Introductionmentioning
confidence: 99%
“…objective) should be taken into account and corrected for. The Brasselet group provided a very useful and detailed description in this sense, proposing an effective calibration procedure of the polarization response of a microscope set-up [77]. The Psaltis group has studied the difference in emission when circular polarization is used instead of linear one for excitation [76], and reported that the nonlinear response under circularly polarized excitation is generally inferior in intensity to the average of linear excitations over all orientations.…”
Section: Polarization Propertiesmentioning
confidence: 99%
“…Moreover, the dielectric layers on dichroic mirrors can be birefringent, in addition to enhancing or suppressing S vs. P polarization modes depending on the orientation relative to the incident beam [121123]. Finally, simply focusing light through a high-NA objective can significantly alter the polarization state in the focal plane [122, 124, 125]. These effects can be compensated for in order to achieve the desired polarization in the sample [123, 126].…”
mentioning
confidence: 99%